Motivating Factors to the Success of Youth Enterprise Startups: A Study of Nepali Enterprises - Kafle, Roshni (Janabhawana Research Journal, 2024)
Youth entrepreneurship emphasizes enterprising qualities such as initiative, innovation, creativity, and risk-taking in the work environment using appropriate knowledge and skills necessary for success in a given environment and culture. The research work is expected to provide a breakthrough in studying youth-centric entrepreneurial and new venture creation efforts as the majority of studies put youth and adult entrepreneurs with substantial experience and exposure into the same basket. The objective of this study is to assess the impact of entrepreneur’s exposure, government entrepreneurial policy and support, banking/ finance accessibility, risk propensity, and family and social support, training and education on the motivation of youth enterprise startup. The study is based on descriptive and analytical research design. Data was collected in Kathmandu Valley through structured questionnaire from 140 respondents which includes various entrepreneurs from Kathmandu Valley. The study used convenience sampling technique for the selection of sample respondents. Various statistical tests such as Karl Pearson’s correlation, and regression analysis were conducted to analyze the data with the help of statistical software SPSS. It was found that entrepreneurial exposure and training and education are the significant factors impacting the motivation of youth entrepreneurship startups. The youth startups seem particularly vulnerable to failure due to the lack of motivation and support and a conducive environment. Moreover, the skill set of conducting interaction of business ideas is an added advantage that comes as a result of entrepreneurial exposure and is key for the success of youth enterprise startups and further implied to government and managerial perspectives.